An Analysis Study of the Utilisation of Digital Learning Media in the Implementation of Microteaching Biology - Rina Astuti; Nadya Shafa Kamila; Duta Saksena Mahatama (International Journal of Educational Technology and Society, 2024)
Microteaching is a simulation or training for prospective teachers to explore the ability of skills in teaching that combines the components of learning. The purpose of this study was to analyse the implementation of microteaching learning in terms of the use of various biology learning media with a touch of technology. The method used is descriptive quantitative with observation sheets and interviews. This research uses a squential explanatory design that combines quantitative and qualitative methods sequentially the first stage of collecting and analysing quantitative data followed by collecting and analysing qualitative data to help explain quantitative results. The results of the study regarding the pattern of using technology-based learning media showed that PowerPoint 92% and learning videos 78% were the most widely used media in microteaching practice. While the level of effectiveness of the media used varies. The 4.6% digital microscope showed a high level of effectiveness even though the frequency of use was still low. This indicates that high technology-based learning media has considerable potential in improving the quality of learning. Furthermore, the analysis of students’ digital competence shows that 70% of students have good to very good mastery of technology. Furthermore, creativity in media development shows an even distribution while time management is still a challenge for 35% of students at a sufficient or insufficient level. The use of technology-based learning media in micro teaching has considerable potential, but still faces several challenges. A systematic and comprehensive approach is needed to optimise the use of technology in developing the teaching competence of prospective biology teachers.